Surface Diffusion on Stressed Solid Surface (Communications in Computational Physics, 2007)
The surface diffusion of an axi-symmetric solid, a whisker, subject to applieduniaxial stress, is studied numerically based on a new boundary integral formulationfor periodic stress configurations. An efficient semi-implicit time-stepping scheme isdeveloped to treat the serve stiffness due to high-order derivatives. When the initialperturbation is small the effect of the stress on the motion of the whisker is found toagree with the linear stability analysis. Numerical simulations of a fully nonlinear caseare also presented, and a potential break-up of the whisker is observed.